Giras de pretos-velhos em um terreiro de umbanda : lugares e eventos de construção de memórias afro-brasileiras - Nascimento, Maria Sampaio do (2017)
The present research analyzes the memories of cambones (assistants) related to the knowledge and belief in the healing powers of the Black Old Entities. In order to organize the work was necessary to understand the concept of memory for a deepening in the reports of the entities as people whom in the past lived in Brazil as slaves and today they are divinized spirits present in the rites of Umbanda at Love's Apprentices Umbanda Group. The Preto-Velho's gira (work) refers to the narratives that support the understanding of what their lives were in captivity and how mediums, from incorporation, update meanings through these religious ritual. During the survey interviews and informal conversations were made with Pretos-Velhos and cambones, as well as interviews with the Pai de Santo (Father of Saint) and the Pai Pequeno (Little Father) of the terreiro (yard). From the experience of the gira was possible to observe characteristic elements of the entities regarding the culture, religion and also the performance of the incorporated mediums. One fact observed during ethnography was the difference between the Pretos-Velhos and other entities, such as the Caboclos, Exus and Pomba Giras, in the form of treatment during the consultations. Entities and consultants demonstrate a family connection, in which the Pretos-Velhos are treated as "grandma", "grandpa", "mother" and "father." Consultants are then called "sons" or "daughters" by strengthening ties between the participants in the dialogue. In the remarks of the rituals was noticed that at any moment the guides demonstrate the behavior of enslaved. They pass on their knowledge as a way of rescuing their ancestral healing practices brought from the African diaspora. The observation based on the experiences lived during the ethnographies was the devotion on the part of the visitors of the terreiro surveyed in relation to the Pretos-Velhos, and at any moment there is perception of submission by the entities, what demonstrates the resistance of the slaves in the past and the affirmation of his seniority in contemporary times.